The Implications of Religious Moderation on the Use of Loudspeakers in Places of Worship - Khadijah, Siti; Siregar, Husna Sari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study looks at implementation moderation in religion values in the use of loudspeakers at Amal Sholeh Mosque, located within a multicultural community. The primary focus is on the responses and perceptions of both Muslim and non- Muslim residents regarding the use of loudspeakers, as well as the extent to which the principles of religious moderation are reflected in interreligious social relations. A qualitative approach was employed, utilizing in-depth interviews and field observations. The findings indicate that although the term “Religious Moderation” is not widely recognized by the local community, its core values such as tolerance, mutual respect, and peaceful coexistence are evident in their daily practices. Nevertheless, complaints persist regarding the direction and volume of the loudspeakers, which are perceived as disturbing. Therefore, it is necessary to disseminate the technical regulations issued by the Ministry of Religious Affairs and to enhance collective awareness in order to foster a harmonious worship environment without compromising the comfort of surrounding residents.